2021
DOI: 10.1101/2021.11.02.21265785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Genetic Model for Central Chondrosarcoma Evolution Correlates with Patient Outcome

Abstract: The treatment options for central chondrosarcoma are limited, and prognoses are generally unreliable. The presence and absence of mutations in IDH1, and IDH2 are defining events, and TERT mutations have been recently been associated with poor outcome. Despite this, molecular biomarkers are lacking. Here, analysing data from 356 patients, comprising results from whole genome sequencing (n=68), digital droplet PCR (n=346), and methylation arrays (n=57), we present a comprehensive genetic analysis of chondrosarco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
2
0
2
Order By: Relevance
“…Further studies are needed to elucidate the mechanism and biological consequences of reduced and altered IDH-associated hypermethylation in DDCS. On the other hand, a recent study in central CS suggested that IDH-mutant tumors displayed significantly higher degree of global hypermethylation compared with IDH-mutant and IDH-wildtype tumors (40). Future studies looking into the differences in the methylation landscapes between IDH versus IDH-mutant DDCS may offer additional insights into the biology of different DDCS subtypes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further studies are needed to elucidate the mechanism and biological consequences of reduced and altered IDH-associated hypermethylation in DDCS. On the other hand, a recent study in central CS suggested that IDH-mutant tumors displayed significantly higher degree of global hypermethylation compared with IDH-mutant and IDH-wildtype tumors (40). Future studies looking into the differences in the methylation landscapes between IDH versus IDH-mutant DDCS may offer additional insights into the biology of different DDCS subtypes.…”
Section: Discussionmentioning
confidence: 94%
“…One study indicated that IDH/IDH mutations are associated with improved PFS but not OS in high-grade CS (39). Another recent study in central CS showed that although TERT mutations occur more frequently in IDH-mutant compared with IDH-mutant tumors, they are associated with worse survival in IDH-mutant but not IDH-mutant tumors (40).…”
Section: Discussionmentioning
confidence: 99%
“…Аберрации гена IDH1, повидимому, встречаются примерно в 50 % случаев. Дедифференцированная хондросаркома у пожилых пациентов чаще локализуется в бедренной кости и тазе и связана с худшим прогнозом по сравнению с обычными вариантами данной опухоли [7,8].…”
Section: Introductionunclassified
“…Результаты CGH и LOH показали, что оба компонента потеряли одну и ту же копию 13-й хромосомы. Эти исследования подтвердили, что нехрящевой компонент высокой степени злокачественности возникает из предыдущего хрящевого компонента [7,9,10].…”
Section: Introductionunclassified